The methodological and theoretical foundations of decision support - Arnott, David; Pervan, Graham (ANU E Press, 2007)
Decision support systems (DSS) is the part of the information systems (IS) discipline that is focused on supporting and improving managerial decision making. The field covers personal DSS, group support systems, negotiation support systems, intelligent DSS, knowledge management-based DSS, executive information systems/business intelligence, and data warehousing. Our long-term project on the intellectual foundations of DSS research has revealed a conservative field that needs to re-orient its research agendas to achieve greater quality and impact. This paper furthers this project and explores what we feel may be at the core of the field’s problems — its methodological and theoretical foundations. A number of recommendations for improving the quality and relevance of DSS research are made. As DSS is a significant proportion of IS research, the lessons and recommendations from this study may be of use to all IS researchers.